A Retrospective Clinical Audit of Bracket Failure among Patients Undergoing Orthodontic Therapy. (15th December 2020) - Kafle, Dashrath; Mishra, Rajeev Kumar; Hasan, Md Riasat; Saito, Takashi
Abstract : Objective . Bonding failure is a problem in orthodontic therapy and has been associated with orthodontic emergencies and delayed treatment time. The aim of this study is to determine the bracket failure rate among patients undergoing orthodontic therapy. Materials and Methods . From the archives of posttreatment records, 200 total cases were selected, out of which 122 cases had detailed treatment records. Cases with incomplete records, large restorations, or enamel aberrations were excluded from the study. Descriptive statistics were applied to obtain sample characteristics, and a chi-square test was applied to compare the bracket failure between different categories. Result . Out of the 122 samples enrolled in the study, female and male patients comprised 71% and 29%, respectively. Class I malocclusions were the most common problem (56%), followed by Class II (41%) and Class III (3%). The bracket failure rate was 3.43%, and 32% of the patients had an incidence of bracket failure. There was no significant difference in bracket failure among genders (p = 0.344 ), malocclusion types (p = 0.191 ), or operators (p = 0.188 ). The maxillary left quadrant was the most common site of bracket failure, followed by the mandibular right quadrant. Conclusion . Bracket failure is relatively uncommon. It is not affected by the gender or age of the patient or by malocclusion type. The maxillary left and mandibular right quadrants are the most common sites of bracket failure.